Fractional Model-Based Formation Control of Quad-Rotor UAVs Using Sliding Mode Backstepping - Khaled Saeed Bin Gaufan; Sami El-Ferik; Nezar M. Alyazidi (IEEE Access, 2024)
Multi-agent systems (MAS) are composed of multiple autonomous agents that interact and collaborate to achieve common objectives. These systems are characterized by their decentralization, scalability, robustness, and the local perspectives of individual agents. In the realm of quadrotor applications, MAS can perform complex tasks such as formation flying, surveillance, search and rescue, and cooperative payload transport. The control of such systems often involves techniques like trajectory planning, consensus algorithms, formation control, and obstacle avoidance. This study introduces a multi-agent quadrotor system controlled using sliding mode backstepping control (SMBC), which combines the advantages of backstepping and sliding mode control to ensure stability and robustness. The novel aspect of this research is the transformation of the leader quadrotor into a fractional-order system (FOS) while maintaining the followers as integer-order systems, all controlled using the same SMBC method. MATLAB simulations validate that the fractional-order leader (FOL) achieves superior trajectory tracking compared to the integer-order leader. Furthermore, the followers tracking the fractional-order leader exhibit enhanced performance, with reduced tracking errors and quicker response times. These findings demonstrate the potential advantages of incorporating fractional-order dynamics into multi-agent control systems.